Влияние модификации поверхности на параметры локализации деформации в сплаве Al — 4% Cu; Известия вузов. Физика; Т. 58, № 6-2 - Лунёв А. Г. Алексей Геннадьевич; Надежкин М. В. Михаил Владимирович; Тересов А. Д. Антон Дмитриевич; Петрикова Е. А. Елизавета Алексеевна (2015, 2015)
Заглавие с экрана